A longitudinal analysis of an accelerating effect of empowerment on job satisfaction: Customer-contact vs. non-customer-contact workers. (August 2016) - Lee, Gyumin; Kim, Peter Beomcheol; Perdue, Richard R.
Abstract: The primary purpose of this paper is to examine whether the impact of empowerment on job satisfaction increases as time changes, and whether this impact is stronger for customer-contact employees than non-customer-contact employees. This study employs a Hierarchical Linear Modeling (HLM) technique to test research hypotheses using a longitudinal dataset from an annual employee opinion survey conducted by a hospitality company in the United States for three consecutive years; 67 work teams consisting of 1534 employees are the unit of analysis. This study finds that the effect of empowerment on job satisfaction is more salient for customer-contact employees, and the effect of empowerment accelerates over the years regardless of the nature of work. Implications of the findings are discussed for researchers and industry practitioners alike.